2015
DOI: 10.1007/s11284-015-1266-2
|View full text |Cite
|
Sign up to set email alerts
|

Combining field observations and laboratory experiments to assess the ecological preferences ofTanymastix stagnalis(L., 1758) (Crustacea, Branchiopoda) in Mediterranean temporary ponds

Abstract: Malladas de El Saler is a mosaic of dune slacks scattered along a coastal sand bar in the Mediterranean region. Active populations of the fairy shrimp T. stagnalis are exclusively present in one of these ponds. We combined field observations and laboratory experiments to find the ecological requirements of T. stagnalis that determine this habitat exclusiveness and the possibility of future establishment in nearby ponds. Conductivity revealed as a determinant ecological constraint. In the field, the species was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…comm.). The relatively short period (15-20 days) occurring between pond filling and the observation of mature individuals suggests that L. jebalae typically occurs of early stages of the flooding cycle, as reported for Linderiella baetica, Tanymastigites lusitanica and Tanymastix stagnalis (Alonso and García-de-Lomas, 2009;Machado and Sala, 2013;Olmo et al, 2015). During periodic samplings, we observed that L. jebalae was absent two months after pond filling, suggesting a short life span, which is also true for Tanymastix stagnalis (1-2.75 months) (Olmo et al, 2015;Lopes da Cunha et al, 2021) and L. baetica (~2 months; Alonso and García-de-Lomas, 2009).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…comm.). The relatively short period (15-20 days) occurring between pond filling and the observation of mature individuals suggests that L. jebalae typically occurs of early stages of the flooding cycle, as reported for Linderiella baetica, Tanymastigites lusitanica and Tanymastix stagnalis (Alonso and García-de-Lomas, 2009;Machado and Sala, 2013;Olmo et al, 2015). During periodic samplings, we observed that L. jebalae was absent two months after pond filling, suggesting a short life span, which is also true for Tanymastix stagnalis (1-2.75 months) (Olmo et al, 2015;Lopes da Cunha et al, 2021) and L. baetica (~2 months; Alonso and García-de-Lomas, 2009).…”
Section: Discussionmentioning
confidence: 61%
“…Thus, the total number of cysts produced in L. jebalae may be higher than those reported here, and multiple clutches or cyst release events throughout the flood cycle are expected, as occurs in other anostracan species (Atashbar et al, 2012;Gharibi et al, 2016). Cyst production reaches 533-545 cysts/female in Branchipus schaefferi (Beladjal et al, 2007); up to 187 cysts/female in Tanymastix stagnalis (Olmo et al, 2015); 579-1094 cysts/female (for 12-18 ºC) in Branchinecta orientalis (Atashbar et al, 2012); about 150-200 eggs per brood in Streptocephalus torvicornis (Nagorskaya et al, 2004); and 174-114 cysts/female (for 20-25 ºC) in Phallocryptus spinosus (Gharibi et al, 2016). Despite other biotic and abiotic factors involved in species prevalence, fecundity may have conservation implications, suggesting that L. jebalae has a greater dispersal potential than L. baetica.…”
Section: Discussionmentioning
confidence: 99%
“…Algerian T. stagnalis populations live in arable sandy pools located in shady areas, with subhumid/humid climate close to the Mediterranean Coast. This type of habitats, especially ponds of costal sand bar, is very similar to that of Spanish populations (Olmo et al 2015). T. stagnalis has been reported to live in temporary pools on sandy soil (Brtek and Thiéry 1995;Zarattini et al 2017), karst systems (Mura and Zarattini 2000), rock pools (Rabet 1994;2001), pools in forests (Gauthier 1928;Rabet 2001) and also in tree holes (Jocque et al 2013).…”
Section: Ecological Notesmentioning
confidence: 52%
“…It was recorded from December to April at temperatures between 14°C and 22°C in Réghaia pools (Gauthier 1928). In Spain it develops in spring only (Olmo et al 2015), while in Italy, it was found in spring after melting snow (Mura and Zarattini 2000) and also, in autumn after the rst rains (Zarattini et al 2017). In France, it occurs throughout the year in the rock pool of the Fontainbleau forest (Rabet 2001).…”
Section: Ecological Notesmentioning
confidence: 99%
“…However, these two species differ in their geographic range size: B. cortesi is an Iberian endemic thought to be a Tertiary relict (Alonso & Jaume, 1991) while T. stagnalis has a widespread distribution ranging from Scandinavia, Ireland, and south-western (SW) Russia to southern Europe and northern Africa (Algeria) (Brtek & Thiéry, 1995;Samraoui & Dumont, 2002;Young, 1976). Besides their different geographic ranges, the two species show similar strategies (Brendonck, 1996) and their life-history traits differ little (in terms of life span, time to reach maturity or hatching time) being characterised by differences among populations according to local environmental conditions (Cristo et al, 2002;Gascón et al, 2012;Mura, 1991;Mura & Zarattini, 2000;Olmo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%